Evaluation of postpartum HIV superinfection and mother-to-child transmission. (31st July 2015) - Redd, Andrew D.; Wendel, Sarah K.J.; Longosz, Andrew F.; Fogel, Jessica M.; Dadabhai, Sufia; Kumwenda, Newton; Sun, Jin; Walker, Michael P.; Bruno, Daniel; Martens, Craig; Eshleman, Susan H.; Porcella, Stephen F.; et al.
<x xml:space="preserve">Abstract</x> Objective: This study examined HIV superinfection in HIV-infected women postpartum, and its association with mother-to-child transmission (MTCT). Design: Plasma samples were obtained from HIV-infected women who transmitted HIV to their infants after 6 weeks of age (transmitters, n = 91) and HIV-infected women who did not transmit HIV to their infants (nontransmitters, n = 91). These women were originally enrolled in a randomized trial for prevention of MTCT of HIV in Malawi (Post-Exposure Prophylaxis of Infants trial in Malawi). Methods: Two HIV genomic regions (p24 and gp41) were analyzed by next-generation sequencing for HIV superinfection. HIV superinfection was established if the follow-up sample contained a new, phylogenetically distinct viral population. HIV superinfection and transmission risk were examined by multiple logistic regression, adjusted for Post-Exposure Prophylaxis of Infants study arm, baseline viral load, baseline CD4+ cell count, time to resumption of sex, and breastfeeding duration. Results: Transmitters had lower baseline CD4+ cell counts (P = 0.001) and higher viral loads (P < 0.0001) compared with nontransmitters. There were five cases of superinfection among transmitters (rate of superinfection = 4.7/100 person-years) compared with five cases among the nontransmitters (rate of superinfection = 4.4/100 person-years; P = 0.78). HIV superinfection was not associated with increased risk of postnatal MTCT of HIV after controlling for maternal age, baseline viral load, and CD4+ cell count (adjusted odds ratio = 2.32, P = 0.30). Longer breastfeeding duration was independently associated with a lower risk of HIV superinfection after controlling for study arm and baseline viral load (P = 0.05). Conclusion: There was a significant level of HIV superinfection in women postpartum, but this was not associated with an increased risk of MTCT via breastfeeding.